Ideowy wymiar badań religioznawczych - Sławomir Sztajer, Sławomir Sztajer (Człowiek i Społeczeństwo, 2015)
Ideology is often perceived as an impediment to advancing the scientific study of religion. The rhetoric of scientificity, which is present in many academic publications in religious studies, seems to conceal a fear of a marriage between science and ideology. The article argues that it is neither possible nor necessary to build religious studies freed from ideological influences. It is not entirely possible because no researcher can isolate herself from ideological factors which are a result of his participation in social life. But it is also not necessary because one can conduct careful and rigorous research in some ideological frameworks. There are situations in which the ideological factor can play a considerable and positive role. What is import_ant, however, is to develop an unceasing critique of ideological influences which aims at uncovering and then controlling them both on the scientific and institutional plane.